2022
DOI: 10.1186/s12906-022-03804-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in pregnancy and labour pain: a cross-sectional study from turkey

Abstract: Background This study aimed to determine the prevalence and pattern of complementary and alternative medicine (CAM) use by and attitudes towards CAM of Turkish women during pregnancy and birth. Methods This was a descriptive, cross-sectional study that included 260 women who gave birth in a university hospital. The Personal Information Form and Complementary, Alternative and Conventional Medicine Attitudes Scale (CACMAS) were used as data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…In a study conducted in the United Kingdom, it was found that 57.1% of women used at least one T&CT during pregnancy [ 18 ], and this rate was 91.5% in Palestine [ 34 ], 56.7% in Iraq [ 32 ], 85.2% in Malaysia [ 35 ], 50.7% in Kenya [ 36 ], and 56.92% in Iran [ 21 ]. In the relevant literature, it is seen that the use of T&CT has differed from country to country [ 37 39 ]. It is thought that these differences in results are due to sample dynamics and sociodemographic differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in the United Kingdom, it was found that 57.1% of women used at least one T&CT during pregnancy [ 18 ], and this rate was 91.5% in Palestine [ 34 ], 56.7% in Iraq [ 32 ], 85.2% in Malaysia [ 35 ], 50.7% in Kenya [ 36 ], and 56.92% in Iran [ 21 ]. In the relevant literature, it is seen that the use of T&CT has differed from country to country [ 37 39 ]. It is thought that these differences in results are due to sample dynamics and sociodemographic differences.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the significant predictors affecting T&CT use in the participants were being a person with a high school or higher degree, having an income greater than expenses, having a nuclear family, being on maternity leave, not performing physical exercises, being a smoker, perceiving one’s general health to be very good, getting advice from a nurse in the case of having a complaint, having knowledge about T&CT, and having access to a T&CT practitioner. Studies have shown that women’s educational statuses are among the statistically significant predictors of T&CT use [ 23 , 25 , 37 , 43 , 48 , 50 ]. It is considered that when pregnant women have higher education levels and income levels and when they are employed, their awareness will grow, and hence, the they will learn about and have more positive attitudes toward T&CT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, from a clinical standpoint, it is advantageous and safe to use non-pharmacological palliative treatments for labouring women. According to global estimates, 73% of women utilise no less than one non-pharmacological pain management approach during labour [5]. Nonpharmacological methods for alleviating labour pain encompass a range of techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacological methods for alleviating labour pain encompass a range of techniques. These include deep breathing exercises [5][6][7][8][9], the utilisation of a birthing ball for exercise [10][11][12], engaging in prayer or meditation [8], applying heat therapy [7,13], and back and sacral massages [5][6][7]13]. Others, however, include music therapy [7,14], positions or posture change [5,6], acupuncture [13,15,16], and aromatherapy (use of essential oils) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation